Ferrochelatase is a therapeutic target for ocular neovascularization - Basavarajappa, Halesha D (EMBO Mol Med, 2017)
Ocular neovascularization underlies major blinding eye diseases such as “wet” age‐related macular degeneration (AMD). Despite the successes of treatments targeting the vascular endothelial growth factor (VEGF) pathway, resistant and refractory patient populations necessitate discovery of new therapeutic targets. Using a forward chemical genetic approach, we identified the heme synthesis enzyme ferrochelatase (FECH) as necessary for angiogenesis in vitro and in vivo. FECH is overexpressed in wet AMD eyes and murine choroidal neovascularization; siRNA knockdown of Fech or partial loss of enzymatic function in the Fech (m1Pas) mouse model reduces choroidal neovascularization. FECH depletion modulates endothelial nitric oxide synthase function and VEGF receptor 2 levels. FECH is inhibited by the oral antifungal drug griseofulvin, and this compound ameliorates choroidal neovascularization in mice when delivered intravitreally or orally. Thus, FECH inhibition could be used therapeutically to block ocular neovascularization.